Summertime particulate matter and its composition in Greece. (15th September 2019) - Tsiflikiotou, M.A.; Kostenidou, E.; Papanastasiou, D.K.; Patoulias, D.; Zarmpas, P.; Paraskevopoulou, D.; Diapouli, E.; Kaltsonoudis, C.; Florou, K.; Bougiatioti, A.; Stavroulas, I.; Theodosi, C.; et al.
Abstract: During the summer of 2012 a coordinated field campaign was conducted in multiple locations in Greece in order to characterize the ambient particulate matter (PM) levels, its chemical composition and the contribution of the regional and local sources. PM1, PM2.5 and PM10 samples were collected simultaneously at seven different sites in Greece: an urban and a suburban station in Patras, a suburban station in Thessaloniki, a suburban and an urban background station in Athens, a rural background station at the Navarino Environmental Observatory (NEO) in southwestern Peloponnese and a remote background site at Finokalia in the northeastern part of Crete. The sites were selected to facilitate the estimation of the contribution of the local emission sources and long range transport. Sulfate and organics were the major PM1 components in all sites suggesting that high sulfate levels still remain in parts of Europe. The photochemistry of the Eastern Mediterranean can convert rapidly the emitted sulphur dioxide to sulfate. Our analysis indicated significant sulfate production over the area, with high sulfate levels, especially in the remote site of Finokalia, associated with air masses that had passed over Turkey. There was high regional secondary organic aerosol production dominating organic aerosol levels even in a major city like Athens. High organic aerosol levels were associated with air masses that had crossed the Balkans with a significant biogenic component. The average PM2.5 concentration ranged from 13 to 18 μg m −3 in the different sites. There were unexpected significant gradients in the concentrations of secondary aerosol components in length scales of a few hundred kilometers. The low concentrations of measured PM2.5 nitrate are mostly organic nitrates and supermicrometer nitrate associated with sea-salt and dust. Dust was a significant PM10 constituent in all areas and was quite variable in space showing the importance of the local sources. Highlights: High sulfate levels still remain in parts of Europe. High regional secondary organic aerosol production during summer. Significant spatial gradients in secondary organic aerosol levels. Most of the fine PM nitrates are organonitrates.